2021 American College of Rheumatology Guideline for the Treatment of Rheumatoid Arthritis. Issue 7 (8th June 2021) - Fraenkel, Liana; Bathon, Joan M.; England, Bryant R.; St.Clair, E. William; Arayssi, Thurayya; Carandang, Kristine; Deane, Kevin D.; Genovese, Mark; Huston, Kent Kwas; Kerr, Gail; Kremer, Joel; Nakamura, Mary C.; et al.
Abstract : Objective: To develop updated guidelines for the pharmacologic management of rheumatoid arthritis. Methods: We developed clinically relevant population, intervention, comparator, and outcomes (PICO) questions. After conducting a systematic literature review, the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used to rate the certainty of evidence. A voting panel comprising clinicians and patients achieved consensus on the direction (for or against) and strength (strong or conditional) of recommendations. Results: The guideline addresses treatment with disease‐modifying antirheumatic drugs (DMARDs), including conventional synthetic DMARDs, biologic DMARDs, and targeted synthetic DMARDs, use of glucocorticoids, and use of DMARDs in certain high‐risk populations (i.e., those with liver disease, heart failure, lymphoproliferative disorders, previous serious infections, and nontuberculous mycobacterial lung disease). The guideline includes 44 recommendations (7 strong and 37 conditional). Conclusion: This clinical practice guideline is intended to serve as a tool to support clinician and patient decision‐making. Recommendations are not prescriptive, and individual treatment decisions should be made through a shared decision‐making process based on patients' values, goals, preferences, and comorbidities.